Hubungan Antara Dark Triad Personality dan Kecenderungan Korupsi Karyawan - Limanago, Yuci (Journal of Research and Measurement in Psychology: JPPP, 2020)
The tendency of employee corruption is influenced by several factors both internal and external. One of these internal factors is personality and the focus examined in this study is Dark Triad Personality. This research was conducted on employees of PT. SGI in the East Java area. The number of subjects in this study was 215 people. All subjects have worked at PT. SGI (private company in area East Java) is at least 1 year starting from the operator / administrator level to the manager with an age range from 22-55 years. The results of correlational analysis showed that there was a significant relationship between dark triad of organizational personality and culture and employee corruption tendency (p = 0,032; r = 0,147). The practical implication of this research is that there is an effort that must be made by company management to always selection personality’s new employee, to reduce the tendency of corruption among employees who work in the company.